Reforms, equity and IMF an economist's world - Sengupta, Arjun (New Delhi Har-Anand, 2001)
This book deals with many subjects like Reforms, Equity and IMF. These are addressed to general readers, students and those interested in politics.
Keywords: Economic development; Economists; Economic policy